Haptic Feedback in Motor Hand Virtual Therapy Increases Precision and Generates Less Mental Workload - Ramírez-Fernández, Cristina; Morán, Alberto L.; García-Canseco, Eloísa (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
In this work we show that haptic feedback in upper limb motor therapy improves performance and generates a lower mental workload. To demonstrate this, two groups of participants (healthy adults and elders with hand motor problems) used a low-cost haptic device (Novint Falcon) and a non-robotic device (Leap Motion Controller). Participants conducted the same rehabilitation task by using a non-immersive virtual environment. Results show significant differences for all participants regarding precision on the use of the haptic feedback device. Additionally, participants in the older adult group demonstrated a lower mental workload while using the haptic device (Novint Falcon). Finally, qualitative results show that participants preferred to conduct their therapy exercises by using the haptic device, as they found it more useful, easier to use and easier to learn.